Nautical Tourism Development Model Based on Coastal Community Empowerment and Financial Literacy in Indonesia - SUMANI, Sumani; AWWALIYAH, Intan Nurul; SURYANINGSIH, Ika Barokah; NUGRAHA, Kristian Suhartadi Widi (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The aim of this study is to identify and analyze the internal and external condition that affect tourism development at Payangan beach, Papuma beach, Watu Ulo beach, and Pancer Puger beach as the base for strategy formulation for nautical tourism development model based on coastal community empowerment and financial literacy in Jember regency. The four beaches have internal powers to take advantage of the existing opportunity. The most appropriate strategy to be applied is growth-oriented strategy. Meanwhile, the existing condition appears that institutional and financial literacy become weaknesses on the four beach tourism destinations, therefore defensive strategy is preferable. Both primary data (interview, focus group discussion and questionnaire) and secondary data (study of literature) are employed in this study. By using purposive sampling technique, samples are collected including local coastal community, regional government, tourists, tourism business and related stakeholders. Data analysis is conducted using descriptive statistics analysis, IFAS and EFAS factors analysis, SWOT analysis and AHP analysis. The AHP result showed that the prioritized factors in nautical tourism management including attraction, accessibility, amenities, institutional and financial literacy. The financial literacy factors (knowledge, skills and confidence) and institutional factors are important to be noticed in order to empower coastal community to develop nautical tourism.